(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
Sugar beet is the only agricultural crop in our country that provides raw materials in the production of sugar, which is a valuable food for the population. Another source of plant raw materials in the world for its production is sugarcane, which grows mainly in Latin America. In the United States, Cuba, India, and Brazil, sugarcane production was also considered the only source of sugarcane in the country, where sugarcane production was launched in Ukraine, Russia, France, Germany, the Baltic states, Kazakhstan, and Kyrgyzstan.